Opinions of members of travel agencies about the actions of prevention to DST/HIV/AIDS to the tourists: a reproductive study - Andrea Ramos da Silva; Creso Machado Lopes (Rev Rene)
This study contemplates the analysis of 24 subject of the travel agencies of Rio Branco – Acre – Brazil, with the objective of verifying the opinion of the same ones about the prevention actions to DST/HIV/AIDS to the tourists. We cleared that 75.0% were in the 20-39 year-old, 25.0% had of 1-5 year of service and 70,8% had finished regular school. Of the studied subjects 52.3% metioned DST as being acquired for sexual practice, where the most mentioned diseases were the Aids, Gonorrhea and Syphilis, and that 66.7% mentioned the condon as prevention method, while 79.2% didn’t develop this prevention type with the tourists.